UI/UX Design Optimization to Increase Customer Satisfaction in Online Booking Applications - Dzaky Kencana, Rifqi; Kus Era, Nadia Eka; Hendry (Cattleya Darmaya Fortuna, 2024)
The development of information technology is increasingly rapid, facilitating the exchange of information and business activities through websites. PT Labani is one of the commercial businesses that focuses on providing software development. PT. Labani's website has several shortcomings, especially in terms of poorly structured navigation and unattractive visual design, which has an impact on a less than optimal user experience when ordering PT. Labani online. Based on the questionnaire analysis, users highly value accurate information and attractive visual design when booking a hotel online. These findings support the development of an interface design designed to provide a more structured and informative user experience. This research aims to redesign and improve the UI/UX quality of PT Labani's website by using the User-Centered Design (UCD) method. The research process includes direct observation, understanding the context of use, determining user needs, solution design, and evaluation through ordering scenarios and information presentation. Measurements were made using the System Usability Scale (SUS), which showed initial values of 18 and 39, which then increased to 90 and 81 after design improvements. This research successfully produced a solution in the form of a more structured and informative interface redesign, which contributed to increased user satisfaction.